2020
DOI: 10.3390/cancers12071777
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of CD200R1 mRNA Expression in Head and Neck Squamous Cell Carcinoma

Abstract: Immune system dysfunction is associated with head and neck squamous cell carcinoma (HNSCC) development and progression and immune checkpoint inhibitors have demonstrated substantial survival benefits in platinum-refractory HNSCC; therefore, we examined the prognostic value of immune-related gene (IRG) expression in HNSCC. We analyzed the expression of 82 IRGs in 71 patients with HNSCC enrolled in a feasibility study for a prospective HNSCC biomarker-driven umbrella trial (Korean Cancer Study Group TRIU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The VIPR1 gene is downregulated at the level of LUAD cells and plays a key tumor suppressor role in the progression of LUAD [ 33 ]. The mRNA expression of CD2000R1 was a favorable prognostic factor in patients with non-small cell lung cancer [ 34 ]. The analysis in this study suggested that the VEGFC was a risk factor in LUAD, whereas the rest of the nine genes were protective factors, which aligned with the results shown in the mentioned previously reported research.…”
Section: Discussionmentioning
confidence: 99%
“…The VIPR1 gene is downregulated at the level of LUAD cells and plays a key tumor suppressor role in the progression of LUAD [ 33 ]. The mRNA expression of CD2000R1 was a favorable prognostic factor in patients with non-small cell lung cancer [ 34 ]. The analysis in this study suggested that the VEGFC was a risk factor in LUAD, whereas the rest of the nine genes were protective factors, which aligned with the results shown in the mentioned previously reported research.…”
Section: Discussionmentioning
confidence: 99%
“…Yue Chen1, reported that they developed a prognostic marker to predict the prognosis of both conventional therapy and immunotherapy [25]. Hyun Chang, CD200R1, a variety of immune mechanisms, is related to an immunerich microenvironment with high immune cell estimates [12]. No matter how mutated the germline genetic information, it would reshape the tumor microenvironment functional mechanisms and modulatory genes process [29].…”
Section: Discussionmentioning
confidence: 99%
“…The key challenge was the selection of suitable patients and identi cation effective treatment regimens. To nd out better curative effect and explore more treatments methods, many researchers have reported that the expression of immune-related genes were different among immune cells and in uenced HNSCC patient prognosis [11,12]. Just like cancer-associated broblasts cell (CAFs), a common stromal cell, it has been reported play important roles in HNSCC progression and prognosis, such as participate in tumor cell proliferation, angiogenesis, and immunosuppression [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, many recent studies have reported TOX as a promoting factor for T cell exhaustion [29,30,48,49], while CD200R1 is a favorable prognostic factor [50], suggesting that those samples may show less exhaustion presumably. To further demonstrate that the CD200R1, TOX, and other well-studied genes indeed contribute to T cell exhaustion rather than due to certain diseases and technique factors, we reconducted the WGCNA analysis by removing the T1D dataset (anti-CD3 therapy) (S4 Fig) and confirmed the expressions of corresponding genes in each dataset (S5 Fig) . In detail, the WGCNA analysis revealed the highest positive correlation between exhaustion and the brown module.…”
Section: Plos Onementioning
confidence: 99%